Impact of free tumor clusters on prognosis after resection of pulmonary adenocarcinoma - Morimoto, Junichi; Nakajima, Takahiro; Suzuki, Hidemi; Nagato, Kaoru; Iwata, Takekazu; Yoshida, Shigetoshi; Fukuyo, Masaki; Ota, Satoshi; Nakatani, Yukio; Yoshino, Ichiro (The Journal of thoracic and cardiovascular surgery, 2016)
Pulmonary adenocarcinoma with a micropapillary component (MPC) has aggressive malignant behavior even if resectable. The aim of this study was to determine clinicopathologic features of patients who underwent surgery for pulmonary adenocarcinoma harboring MPCs, with particular focus on coexistent free tumor clusters (FTCs). We retrospectively reviewed 444 patients with pulmonary adenocarcinoma who underwent surgery from March 2007 to July 2013. An MPC was defined as a >5% micropapillary pattern. We also defined FTCs to be a group of more than 3 small clusters containing <20 nonintegrated micropapillary tumor cells that were spreading within air spaces, >3 mm apart from the main tumor. The clinicopathologic characteristics of patients with and without FTCs were retrospectively investigated in MPC-positive patients. MPCs were identified in 67 patients (15.1%), 31 of whom (46.3%) were positive for FTCs. The distance between the furthest edge of FTCs and main tumors did not exceed the diameter of the main tumor in each case (average, 7.3 mm). Locoregional recurrences were frequently observed in FTC-positive patients. FTC-positive patients experienced a significantly lower 5-year recurrence-free survival rate compared with FTC-negative/MPC-positive patients (20.4% vs 52.2%, P < .001). Recurrence-free survival of FTC-negative and -positive patients was equivalent to that of patients with p-T2 and p-T3 MPC-negative adenocarcinoma, respectively. Coexistence of FTCs resulted in a further negative impact on postoperative prognosis among MPC-positive adenocarcinomas and should be considered for upstaging the p-T factor and during evaluation of surgical margins.